(untitled) (Tzintzun, Revista de Estudios Históricos, 2022)
The indigenous rebellion that broke out in Yucatan in July 1847 deeply shook the regional society and detonated intellectual activities with the aim of imposing a vision of the events. The aim of the essay is to unravel the invention of the neologism Caste War, built by different artificers, from historians, journalists, literary or writers in a long period, from the detonation of the internal war conflict until the development of an ultramontane discourse in 1927.